Digital Sphygmomanometer Based on Arduino Using TFT LCD Display - Kusumaningtyas, Yasmine Winda; Indrato, Tri Bowo; Asalim T.P, M.Prastawa; Utomo, Bedjo (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Sphygmomanometer is a human blood pressure measuring device which has several types such as mercury, digital, and aneroid. At this time, mercury Sphygmomanometer is not allowed to be used anymore considering the side effects of mercury which can harm the skin and even respiration. This study helps to reduce the use of mercury type Sphygmomanometer. The researchers make Arduino TFT LCD display based Sphygmomanometer so that the use of mercury can be reduced and make it easier for users to process measurement. The researchers used the oscillometry method in making the device to calculate the systolic and diastolic pressure. The result of blood pressure measurement has a systolic error rate of 0,08% and a diastolic error rate 0,09%.